Ethnography as Commentary Writing from the Virtual Archive - Fabian, Johannes (Duke University Press, 2008)
The Internet allows ethnographers to deposit the textual materials on which they base their writing in virtual archives. Electronically archived fieldwork documents can be accessed at any time by the writer, his or her readers, and the people studied. Johannes Fabian, a leading theorist of anthropological practice, argues that virtual archives have the potential to shift the emphasis in ethnographic writing from the monograph to commentary. In this insightful study, he returns to the recording of a conversation he had with a ritual healer in the Congolese town of Lubumbashi more than three decades ago. Fabian's transcript and translation of the exchange have been deposited on a website (Language and Popular Culture in Africa), and in Ethnography as Commentary he provides a model of writing in the presence of a virtual archive.In his commentary, Fabian reconstructs his meeting with the healer Kahenga Mukonkwa Michel, in which the two discussed the ritual that Kahenga performed to protect Fabian's home from burglary. Fabian reflects on the expectations and terminology that shape his description of Kahenga's ritual and meditates on how ethnographic texts are made, considering the settings, the participants, the technologies, and the linguistic medium that influence the transcription and translation of a recording and thus fashion ethnographic knowledge. Turning more directly to Kahenga-as a practitioner, a person, and an ethnographic subject-and to the questions posed to him, Fabian reconsiders questions of ethnic identity, politics, and religion. While Fabian hopes that emerging anthropologists will share their fieldwork through virtual archives, he does not suggest that traditional ethnography will disappear. It will become part of a broader project facilitated by new media
Description based on online resource; title from PDF title page (publisher's Web site, viewed 20. Nov 2024)
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Communication and culture; Communication in ethnology; Ethnology -- Authorship; Ethnology -- Computer network resources